Investigating the age effects on subjective assessments of traffic signs - Kurniawan, Sri Hastuti; Zaphiris, Panayiotis (My University, 2001)
Traffic signs function as an aid for drivers on the road. Hence, it is important to ensure that traffic signs are effective. The study investigates whether verbal or pictorial signs felt more forceful and would catch the driver's attention first. Twenty older and twenty younger drivers participated in the study. Eleven verbal signs and eleven of their pictorial versions were tested. Using card-sorting technique, driver's underlying perception of what aspects of traffic signs make them stand out among other signs were also investigated. Based on the statistical analysis results, pictorial signs were found to be superior to verbal ones.
Keywords: Aging; Card sorting; Ergonomics; Human factors; Traffic sign